THE RELATIONSHIP BETWEEN SHIFT WORK AND WORKLOAD WITH WORK FATIGUE IN EMPLOYEES OF INDOMARET CONVENIENCE STORE IN BANDAR LAMPUNG - Siti Adawiah; Hendri Dunan (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Basically, one of the things that can reduce a person's ability to work and one's immune system to work is fatigue from work. Causes include general fatigue, boredom, intensity, length of physical and mental effort, anxiety or disagreement, and perception of pain. In addition, most workers become exhausted due to unscheduled work schedules, heavy responsibilities, and lack of rest. The study aims to determine the relationship between shift work and work fatigue in Indomaret Minimarket employees and the relationship between workload and work fatigue. The study used  a cross-sectional  design that is quantitative. Research samples from 35 workers from seven Indomaret Minimarkets in Teluk Betung, Bandar Lampung. Carried out using Purposive Sampling technique. And data analysis using pearson correlation techniques. The results showed that shift work was positively related to work fatigue and workload was positively related to work fatigue.